Biosynthesis of fatty acids and sterols in relation to the antibiotic formation in Oudemansiella mucida - Nerud, F; Musílek, V (Folia microbiologica, 1978)
The production of mucidin by the basidiomycete Oudemansiella mucida was negatively influenced by the application of D-glucitol as the main carbon source, the effect being independent of the growth rate of the mycelium. The rate of fatty acid synthesis was measured by incorporation of 1-14C-acetate. After 8 days of cultivation, the amount of fatty acids was approximately half that synthetized during cultivation on glucose. The specific rate of incorporation reached its maximum after seven days of cultivation. Incorporation of 2-14C-MEValonate into sterols was the same under the two sets of cultivation conditions. Acetate units from the degraded fatty acids are probably also utilized for antibiotic synthesis.
Keywords: Glucose; Acetates; sorbitol; Agaricales; mastné kyseliny; steroly; Sterols; antibakteriální látky; Anti-Bacterial Agents; Sorbitol; glukosa; Fatty Acids; acetáty